Milk-Derived Tripeptides IPP (Ile-Pro-Pro) and VPP (Val-Pro-Pro) Promote Adipocyte Differentiation and Inhibit Inflammation in 3T3-F442A Cells - Chakrabarti, Subhadeep; Wu, Jianping (PLOS ONE, 2015)
Milk derived tripeptides IPP (Ile-Pro-Pro) and VPP (Val-Pro-Pro) have shown promise as anti-hypertensive agents due to their inhibitory effects on angiotensin converting enzyme (ACE). Due to the key inter-related roles of hypertension, chronic inflammation and insulin resistance in the pathogenesis of metabolic syndrome, there is growing interest in investigating established anti-hypertensive agents for their effects on insulin sensitivity and inflammation. In this study, we examined the effects of IPP and VPP on 3T3-F442A murine pre-adipocytes, a widely used model for studying metabolic diseases. We found that both IPP and VPP induced beneficial adipogenic differentiation as manifested by intracellular lipid accumulation, upregulation of peroxisome proliferator-activated receptor gamma (PPARγ) and secretion of the protective lipid hormone adiponectin by these cells. The observed effects were similar to those induced by insulin, suggesting potential benefits in the presence of insulin resistance. IPP and VPP also inhibited cytokine induced pro-inflammatory changes such as reduction in adipokine levels and activation of the nuclear factor kappa B (NF-κB) pathway. Taken together, our findings suggest that IPP and VPP exert insulin-mimetic adipogenic effects and prevent inflammatory changes in adipocytes, which may offer protection against metabolic disease.